2014
DOI: 10.5951/jresematheduc.45.2.0246
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Characteristics Associated With Mathematics Teachers' Beliefs and Awareness of Their Students' Mathematical Dispositions

Abstract: This study investigates relationships between teacher characteristics and teachers' beliefs about mathematics teaching and learning and the extent to which teachers claim awareness of their students' mathematical dispositions. A professional background survey, a beliefs and awareness survey, and a teacher mathematical knowledge assessment were administered to 259 novice upper-elementary and 184 novice middle-grades teachers. Regression analyses revealed statistically significant relationships between teachers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 100 publications
(91 reference statements)
2
36
0
2
Order By: Relevance
“…Thus, ethnicminority teachers are possibly more likely to find themselves in situations where it becomes more difficult to incorporate non-traditional, constructivist approaches in their instruction (Haberman, 1991), and in turn, this type of environment may influence their epistemic beliefs about mathematics. This finding is consistent with previous research that has found differences between teachers at low socioeconomic status schools versus teachers at high socioeconomic schools in terms of the extent to which they emphasize facts and procedures in their mathematics instruction (Clark et al, 2014;Minor, Desimone, Phillips, & Spencer, 2015). Consistent with this finding, prior research has indicated that racial/ethnic-minority teachers are more likely than White teachers to believe that the focus of mathematics instruction should be on memorization and procedural skills (Clark et al, 2014).…”
Section: Antecedents Of Teachers' Educational Beliefssupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, ethnicminority teachers are possibly more likely to find themselves in situations where it becomes more difficult to incorporate non-traditional, constructivist approaches in their instruction (Haberman, 1991), and in turn, this type of environment may influence their epistemic beliefs about mathematics. This finding is consistent with previous research that has found differences between teachers at low socioeconomic status schools versus teachers at high socioeconomic schools in terms of the extent to which they emphasize facts and procedures in their mathematics instruction (Clark et al, 2014;Minor, Desimone, Phillips, & Spencer, 2015). Consistent with this finding, prior research has indicated that racial/ethnic-minority teachers are more likely than White teachers to believe that the focus of mathematics instruction should be on memorization and procedural skills (Clark et al, 2014).…”
Section: Antecedents Of Teachers' Educational Beliefssupporting
confidence: 90%
“…In addition, since change in knowledge does not occur in isolation, (Loucks-Horsley et al, 2010), one could conceivably argue that as knowledge changes, beliefs also change, and vice versa. Clark et al (2014) found a significant relationship between mathematics teachers' beliefs and mathematical knowledge. Therefore, professional development of teachers that focuses on developing teachers' knowledge and skills may also potentially change teachers' beliefs as it influences their content and pedagogical content knowledge.…”
Section: Professional Development Focused On Mathematics Content Andmentioning
confidence: 85%
See 3 more Smart Citations